Taking distinction practices seriously: Methodological reflections on ethnographic distance in fieldwork with marginalized people - Zhang, Chaoxiong; Zhan, Yang (American anthropologist, 2025)
Anthropologists often consider the distinction from our interlocutors a barrier, assuming that overcoming the distance allows us to understand our interlocutors. Other times, ethnographers intentionally maintain ethnographic distance to avoid “doing harm” to our interlocutors. In either case, ethnographers are assumed to be responsible for maintaining a proper distance from our research participants. As two cultural anthropologists who work with marginalized groups (drug users and rural‐to‐urban migrant workers), we are aware of our emotional, cultural, and epistemological distances from our interlocutors. However, we also notice that our interlocutors often take the initiative to define their distance from us. In this paper, we explore these often‐overlooked distinction practices employed by our research subjects. We view such actions as active negotiation with power relations, rather than passive avoidance. Thus, we propose a shift from merely acknowledging the intrinsic distinctions in the researcher‐researched relationship to learning from and understanding the distinctions created by our interlocutors. We argue that our interlocutors’ agency in these distinction practices is crucial and warrants significant attention in ethnographic research. We further highlight distinction as a valuable method, a way of not only understanding our research subjects but also participating in their world. 摘要 人类学家通常把我们和田野对象的区别, 看作是一种障碍, 并假定克服这种区别和差异, 才能理解我们在田野中遭遇的各类人和事。同时, 民族志学者也有意在田野中和我们的对话者保持距离, 避免 “伤害 ”我们的对话者。无论上述哪种情况, 民族志学者承担着与我们的研究对象保持适当距离的责任。作为两名与边缘化群体(毒 品者和从农村到城市的农民工)打交道的文化人类学家, 我们在工作中意识到自己与对话者在情感、文化和认识论上的距离。然而, 我们也注意到, 我们的田野对象也经常主动界定她们与我们的距离。在本文中, 我们探讨田野中的研究对象主动与研究者保持距离的实践和情境。我们认为这些区隔实践是对权力关系的主动协商, 而不是被动回避。因此, 我们提出仅仅承认研究者与被研究者之间的内在区别是不够的, 我们需要理解田野对象所采取的区隔实践。我们认为, 田野对象在这些实践中的能动性至关重要, 值得在人类学的研究中被高度重视。我们进一步强调, 区隔实践是一种有价值的方法, 它不仅是了解研究对象的一种方式, 也是参与其世界的一种方式。 [民族志、田野工作、区隔实践、边缘化、中国] Resumen Los antropólogos a menudo consideran la diferenciación de nuestros interlocutores como una barrera, asumiendo que el superar la distancia nos permite entender a nuestros interlocutores. Otras veces, los etnógrafos mantienen intencionalmente la distancia etnográfica para evitar “hacer daño” a sus interlocutores. En cualquier caso, se asume que los etnógrafos son responsables por mantener una distancia apropiada de los participantes de nuestra investigación. Como dos antropólogos culturales que trabajan con grupos marginados (consumidores de drogas) y trabajadores migrantes de lo rural a lo urbano), somos conscientes de nuestra distancia emocional, cultural y epistemológica de nuestros interlocutores. Sin embargo, también notamos que nuestros interlocutores a menudo toman la iniciativa para definir su distancia de nosotros. Este artículo explora estas prácticas de distinciones a menudo pasadas por alto empleadas por nuestros sujetos de investigación. Vemos tales acciones como negociación activa con relaciones de poder en vez de un evitar pasivo. Así, proponemos un cambio de escasamente reconocer las distinciones intrínsecas en la relación investigador‐investigado a aprender de, y entender las distinciones creadas por nuestros interlocutores. Argumentamos que la agencia de nuestros interlocutores en estas prácticas de distinción es crucial y justifica una atención significativa en la investigación etnográfica. Además, destacamos la distinción como un método valioso, una manera no solo de entender nuestros sujetos de investigación sino también de participar en su mundo. [etnografía, trabajo de campo, prácticas de distinción, marginalización, China]